2004
DOI: 10.1080/08880010490501097
|View full text |Cite
|
Sign up to set email alerts
|

Which Babies Get Blood in Jos-Nigeria?

Abstract: Documentation of the transfusion needs of neonatal units is required to guide blood banks in meeting demands. A prospective observational study of newborn transfusions over 35 weeks was conducted. Eighty-four transfusions were conducted in 62 of 377 (16.45%) admitted infants in 35 weeks. Neonatal jaundice (57.2%) and anemia (38.1%) were main indications. In 85.7% cases, blood transfused was < 3 days old. Weight of infants at transfusion was < 2500 g in 51.6% cases. Infants were first transfused at < 7 days in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
2
4
0
Order By: Relevance
“…This was relatively higher than the rate of one out of every six, reported earlier from Jos, Nigeria. [8] Similarly, the rate of 4.8 transfusions per week observed in the present study was high indicating a great utilization of blood and transfusion services in our unit. The transfusion rate in our unit was also double the rate of 2.4 transfusions per week previously reported from Jos, Nigeria.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This was relatively higher than the rate of one out of every six, reported earlier from Jos, Nigeria. [8] Similarly, the rate of 4.8 transfusions per week observed in the present study was high indicating a great utilization of blood and transfusion services in our unit. The transfusion rate in our unit was also double the rate of 2.4 transfusions per week previously reported from Jos, Nigeria.…”
Section: Discussionsupporting
confidence: 66%
“…The transfusion rate in our unit was also double the rate of 2.4 transfusions per week previously reported from Jos, Nigeria. [8] It is not certain why we recorded double the rate of Jos at our center, but we speculate that it might be due to the fact that most of the babies studied in our center were referred. Previous studies had shown that referred babies were at a higher risk for morbidities.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Within the cesarean section–only studies, placenta previa at 27% (47 of 431) and obstructed labor at 25% (44 of 431) were the leading indications for transfusion. Among newborn babies, WB and RBC products were used in relatively equal measure, and neonatal jaundice and bleeding together accounted for 66% (218 of 477) of the products transfused overall …”
Section: Resultsmentioning
confidence: 99%
“…These 10 studies were used for the primary outcome calculation. The rest of the studies evaluated blood use among specific patient groups: nine studies among pediatric patients only; five on obstetrics and gynecology patients; three among cesarean section deliveries; three among newborn babies; two among elective surgical operations; two exclusively on the use of platelets; two on the use of autologous blood; and one among hepatogastroenterology patients . Most studies made a clear distinction between the number of patients transfused and the number of blood products used for transfusion.…”
Section: Resultsmentioning
confidence: 99%